The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3847/0004-637x/823/2/76
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Molecular and Atomic Gas Phases in the Milky Way

Abstract: We analyze radial and azimuthal variations of the phase balance between the molecular and atomic interstellar medium (ISM) in the Milky Way (MW) using archival CO( J=1-0) and HI 21 cm data. In particular, the azimuthal variations-between the spiral arm and interarm regions-are analyzed without any explicit definition of the spiral arm locations. We show that the molecular gas mass fraction, i.e.,, varies predominantly in the radial direction: starting from~100% at the center, remaining 50% toR 6 kpc and dec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 102 publications
(192 reference statements)
7
49
0
Order By: Relevance
“…the conversion of total gas mass to stars) to decrease within this radius, but it is not clear how this might relate to the rate of production of stars in dense clumps measured by the SFF. Koda et al (2016) show that the molecular gas fraction increases steadily with decreasing RGC, but we see in Figure 2 that the surface density of mass in dense clumps falls rapidly within 4 kpc (Bronfman et al 1988;Urquhart et al 2014a). The production of molecular clouds from neutral gas therefore is more efficient at small RGC where the H2/HI ratio is nearly 100% (Koda et al 2016).…”
Section: What Drives the Gradient In Sff With Rgc?mentioning
confidence: 98%
See 1 more Smart Citation
“…the conversion of total gas mass to stars) to decrease within this radius, but it is not clear how this might relate to the rate of production of stars in dense clumps measured by the SFF. Koda et al (2016) show that the molecular gas fraction increases steadily with decreasing RGC, but we see in Figure 2 that the surface density of mass in dense clumps falls rapidly within 4 kpc (Bronfman et al 1988;Urquhart et al 2014a). The production of molecular clouds from neutral gas therefore is more efficient at small RGC where the H2/HI ratio is nearly 100% (Koda et al 2016).…”
Section: What Drives the Gradient In Sff With Rgc?mentioning
confidence: 98%
“…Koda et al (2016) show that the molecular gas fraction increases steadily with decreasing RGC, but we see in Figure 2 that the surface density of mass in dense clumps falls rapidly within 4 kpc (Bronfman et al 1988;Urquhart et al 2014a). The production of molecular clouds from neutral gas therefore is more efficient at small RGC where the H2/HI ratio is nearly 100% (Koda et al 2016). The fraction of molecular gas in the form of dense clumps within these clouds, while more or less steady, on average outside ∼4 kpc, albeit with very large, apparently random variations from cloud to cloud (Eden et al 2012(Eden et al , 2013, falls sharply inside this radius.…”
Section: What Drives the Gradient In Sff With Rgc?mentioning
confidence: 98%
“…There are no high-resolution HI data of M100 that allow us to distinguish the armto-inter-arm variation; these data are not available for most of the nearby galaxies also. Nonetheless, gas phase change between the arm and inter-arm regions has been observed in the Milky Way (Koda et al 2016). Interstellar gas becomes molecular as it enters spiral arms, but is dissociated back to the atomic phase upon leaving the arms.…”
Section: Kennicutt-schmidt Relationmentioning
confidence: 99%
“…Recently Rice et al (2016) have shown that the brightest molecular clouds seem to be spatially correlated with the spiral structures of the Galaxy. On the other hand, Koda et al (2016) showed that there is rather modest variation of the fraction of molecular to atomic gas (about 20%) between the arm and the interarm regions of the Milky Way. These authors noticed that the main change in gas phase occurs at R gal > 6 kpc where the molecular fraction drops below 50% (see Figure 9, bottom left panel).…”
Section: Face-on Viewmentioning
confidence: 99%
“…At larger R gal , the H i surface density falls exponentially with a scale length of R HI ≈ 3.75 kpc (Kalberla & Kerp 2009). Both Nakanishi & Sofue (2016) and Koda et al (2016) showed that the fraction of the gas in molecular form, f H2 = Σ H2 /(Σ HI +Σ H2 ), declines steadily with R gal . This is also shown in the bottom left panel of Figure 9 using our estimate of Σ H2 .…”
Section: Surface Density Versus Galactic Radiusmentioning
confidence: 99%